Paradigma Ulama dalam Penentuan Kualitas Hadis dan Implikasinya dalam Kehidupan Umat Islam - Mujibatun, Siti (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
Internal religious conflicts in the practice of religion in daily life in Islam is prompted by, among others, different schools of thought among the scholars of hadith from the early Islamic period to the present, especially in determining the quality of the hadith as hujjah syar’iyyah. The type of this research is the research library. Data sources are documents consists of: The Book of Hadith Sciences History, Introduction to Hadith, Science of Mustalah al- Hadith, the book of al-Jarh wa al-ta’dil, hadith collection books (kutub al- tis’ah) and their commentaries. Research findings are as follows: a). There are four schools of scholars in determining the quality of the hadith, namely, mutasyaddid (strict) muta’annut (excessive), mutawassit (moderate) and mutasahhil (permissive). b). the school mutasyaddid implies that hadith which do not meet the standard of validity may not be used as hujjah syar’iyyah. The school of mutawassit share this view, noting that unless there is a theorem (from Quran or Hadith) supporting it. The schools of muta’annut and mutasahhil tend to accept hadith with dhaif quality as reference for the purpose of moral virtue.